2012
DOI: 10.1017/s000748531100085x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and polymorphism analysis of phosphoglucose isomerase gene in the fall webworm (Hyphantria cunea)

Abstract: Phosphoglucose isomerase (PGI) plays an important role in energy metabolism, and it is documented that PGI exhibits an extensive polymorphism which can affect insects' fitness and adaptation. In this paper, we studied the structural characteristics and polymorphism of pgi gene in the fall webworm (Hyphantria cunea), an important invasive pest in some European and Asian countries. A 2110-bp pgi full-length cDNA encoding a polypeptide of 556 amino acids was obtained from H. cunea. The pgi full-length in the H. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The robust adaptability of the fall webworm probably results from its high polyphagy and reproductive capability. Fall webworms feed on more than 600 species of trees and shrubs 5 and adult females may lay as many as 900 eggs each 6 . As the name denotes, the fall webworm also is a remarkable web-maker, and newly emerged larvae construct massive silk web nests to increase their survival by facilitating feeding and escaping natural enemies ( Supplementary Fig.…”
mentioning
confidence: 99%
“…The robust adaptability of the fall webworm probably results from its high polyphagy and reproductive capability. Fall webworms feed on more than 600 species of trees and shrubs 5 and adult females may lay as many as 900 eggs each 6 . As the name denotes, the fall webworm also is a remarkable web-maker, and newly emerged larvae construct massive silk web nests to increase their survival by facilitating feeding and escaping natural enemies ( Supplementary Fig.…”
mentioning
confidence: 99%
“…Although synonymous substitutions are often considered silent because the amino acid is not modified, they can affect transcription, splicing, mRNA transport, and translation, any of which could alter phenotype. Molecular studies on Pgi in the fall webworm [Hyphantria cunea (Drury)] found five non-synonymous mutation sites, one of which changed the hydrophobicity of the glycosaminoglycan attachment site (Luo et al, 2012). A similar scenario could be occurring in the 54F line of C. floridanum, impacting enzyme activity but not altering enzyme charge, our only way of detecting allelic variation.…”
Section: Discussionmentioning
confidence: 93%
“…Molecular studies on Pgi in the fall webworm [Hyphantria cunea (Drury)] found five non-synonymous mutation sites, one of which changed the hydrophobicity of the glycosaminoglycan attachment site (Luo et al, 2012). One possible explanation is that there is 'cryptic' synonymous or non-synonymous variation in the Pgi allele of line 54F that functionally distinguishes it from the alleles of the other Pgi 54 lines, even though the charge of its enzyme product makes it electrophoretically indistinguishable.…”
Section: Discussionmentioning
confidence: 99%
“…sHSPs may also act as chaperone proteins for promoting tissue and organ degradation and remodeling during the pupal stage [7]. Hyphantria cunea demonstrates a remarkable reproductive capacity, characterized by an average fecundity of 800-900 eggs per female and a maximum potential of up to 2000 eggs [47]. High expression of sHSPs may be involved in the reproductive events of adults, including the development of the reproductive system and the formation of germ cells [48].…”
Section: Discussionmentioning
confidence: 99%